Synergistic inactivation of bacteria based on a combination of low frequency, low-intensity ultrasound and a food grade antioxidant - Cuong Nguyen Huu; Rewa Rai; Xu Yang; Rohan V. Tikekar; Nitin Nitin (Ultrasonics Sonochemistry, 2021)
This study evaluated a synergistic antimicrobial treatment using a combination of low frequency and a low-intensity ultrasound (LFU) and a food-grade antioxidant, propyl gallate (PG), against a model gram-positive (Listeria innocua) and the gram-negative bacteria (Escherichia coli O157:H7). Bacterial inactivation kinetic measurements were complemented by characterization of biophysical changes in liposomes, changes in bacterial membrane permeability, morphological changes in bacterial cells, and intracellular oxidative stress upon treatment with PG, LFU, and a combination of PG + LFU. Combination of PG + LFU significantly (>4 log CFU/mL, P < 0.05) enhanced the inactivation of both L. innocua and E. coli O157:H7 compared to PG or LFU treatment. As expected, L. innocua had a significantly higher resistance to inactivation compared to E. coli using a combination of PG + LFU. Biophysical measurements in liposomes, bacterial permeability measurements, and scanning electron microscope (SEM)-based morphological measurements show rapid interactions of PG with membranes. Upon extended treatment of cells with PG + LFU, a significant increase in membrane damage was observed compared to PG or LFU alone. A lack of change in the intracellular thiol content following the combined treatment and limited effectiveness of exogenously added antioxidants in attenuating the synergistic antimicrobial action demonstrated that oxidative stress was not a leading mechanism responsible for the synergistic inactivation by PG + LFU. Overall, the study illustrates synergistic inactivation of bacteria using a combination of PG + LFU based on enhanced membrane damage and its potential for applications in the food and environmental systems.